Simultaneous muscle water T2 and fat fraction mapping using transverse relaxometry with stimulated echo compensation. (27th January 2016) - Marty, Benjamin; Baudin, Pierre‐Yves; Reyngoudt, Harmen; Azzabou, Noura; Araujo, Ericky C. A.; Carlier, Pierre G.; de Sousa, Paulo L.
Abstract : Skeletal muscle inflammation/necrosis and fat infiltration are strong indicators of disease activity and progression in many neuromuscular disorders. They can be assessed by muscle T2 relaxometry and water‐fat separation techniques, respectively. In the present work, we exploited differences between water and fat T1 and T2 relaxivities by applying a bi‐component extended phase graph (EPG) fitting approach to simultaneously quantify the muscle water T2 and fat fraction from standard multi‐slice multi‐echo (MSME) acquisitions in the presence of stimulated echoes. Experimental decay curves were adjusted to the theoretical model using either an iterative non‐negative least‐squares (NNLS) procedure or a pattern recognition approach. Twenty‐two patients (age, 49 ± 18 years) were selected to cover a large range of muscle fat infiltration. Four cases of chronic or subchronic juvenile dermatomyositis (age, 8 ± 3 years) were investigated before and 3 months following steroid treatment. For control, five healthy volunteers (age, 25 ± 2 years) were recruited. All subjects underwent the MSME sequence and EPG fitting procedure. The EPG fitting algorithm allowed a precise estimation of water T2 and fat fraction in diseased muscle, even in the presence of large B1 + inhomogeneities. In the whole cohort of patients, there was no overall correlation between water T2 values obtained with the proposed method and the fat fraction estimated inside muscle tissues (R 2 = 0.02). In the patients with dermatomyositis, there was a significant decrease in water T2 (‐4.09 ± 3.7 ms) consequent to steroid treatment. The pattern recognition approach resulted in a 20‐fold decrease in processing time relative to the iterative NNLS procedure. The fat fraction derived from the EPG fitting approach correlated well with the fat fraction derived from a standard three‐point Dixon method (≈1.5% bias). The bi‐component EPG fitting analysis is a precise tool to monitor muscle tissue disease activity and is able to handle bias introduced by fat infiltration and B1 + inhomogeneities. Copyright © 2016 John Wiley & Sons, Ltd. Abstract :